Comparative Analysis of Neonatal Intensive Care Units (NICUs) Performance Indicators: A Systematic Review - LOUAZIZ , Hassan; BOUTIB , Amal; ERRABAI , Mouhsine; BARKAT , Amina (Revue Internationale des Sciences de Gestion, 2025)
Objectives: To evaluate the key performance indicators of neonatal intensive care units (NICUs), including length of stay (LOS), neonatal mortality rates, admission and occupancy rates, to identify factors influencing outcomes and resource utilization. Methods: A systematic review was conducted using the PRISMA 2020 guidelines and a pre-registered protocol on PROSPERO (CRD42024612635). Articles published between January 2013 and December 2024 were searched in PubMed, Scopus, and Web of Science. Inclusion criteria focused on observational studies reporting NICU key performance indicators. Two reviewers independently selected articles and assessed their quality using the NHLBI and MMAT tools. Results: Out of 8,416 identified articles, 14 studies were included, representing high-income countries (64.29%) and middle to low-income countries (35.71%). Length of stay (LOS) was longest for preterm and low birth weight newborns, influenced by infections and clinical practices. Neonatal mortality rates ranged from 0.7% for term infants to 6.1% for preterm infants, with improvements linked to interventions like thermoregulation protocols. Admission rates varied by neonatal and maternal characteristics, with preterm infants comprising a significant share. Average occupancy rates highlighted resource utilization challenges, especially for high-risk populations, with quality improvement initiatives showing potential to optimize LOS and reduce overcrowding. Conclusion: his review highlights disparities in NICU performance across different contexts and identifies critical factors influencing outcomes. The findings underscore the importance of targeted strategies to improve neonatal outcomes and optimize resource utilization in NICUs.